شعرية العمران عند عمر بن باحمد هيبةّ (Revue El-Wahat pour les Recherches et les Etudes, 2020)
The Paper Aims To Study In The Valley Of Mzab With The Contemporary Algerian Poet Omar Bin Bahmed Heiba: (The Castle, The Well, The Dam, The Fence And The Tower) An Aesthetic Reading That Matches  The Luxury Of Material Civilization With The Aesthetics Of Style, The Poet Utilized A Language That Senses Beauty, And Incorporated It With Metaphors, Allegories And Similes, In Violation Of The Common  Adage To Be Inserted Into  The Reader’s Feelings And To Deepen His Relationship With These Civil And Human Achievements. He Resorted To The Aesthetic Of Advancing And Delaying In Order To Highlight This Urbanization To The Receiver That It Is Known To The Arabs, If They Singled Out Something With Their Interest They Initiate It, And They Surprised Him By Making Him Meet This Emotional Position Desirable To Them. The Poet Also Cared About Repetition When He Used It To Touch Off The Morality Of Loyalty To This Heritage, And Enrich It To Persue The Presence, Not To Remain Detained In The Past. It Turns Out That The Poet’s Moral Reference Is Earlier Than The Geography Reference, So He Resorted To Religious Intertextuality Especially (The Hadith Of The Prophet) Venting His Desire By Referring This Urban Advantage And Make It Towed To The Sky, And The Poet Employed Two Linguistic Fields; The Field Of Nature By Evoking The Nature Of The South And Its Harmony With Urbanism And The Filed Of Urbanism, What Allowed Him To Penetrate The Poetic Text To Be Turned Into A Poetic Term. Thus, Omar Bin Ahmed Ahmed Heiba, The Poet Of Urbanism, Rightfully Worked On His Humanization And Deepening His Aesthetic Presence. Key Words-  Algerian Poetry, Urbanism, Civilisation Valley Of Mzab, Castle, Omar Heiba.